“We Can Resolve Our Conflict” Conflict Resolution Training Program: Western Thrace Elementary School Sample - Pynar Ali Dai; Arzu Araz (Psikoloji Çalışmaları)
Children do not know how to solve problems with their friends in a constructive manner. They may resort to violence or act passively to avoid conflict. Therefore, violence in communication between children is quite common. Conflict resolution programs are widely used in schools around the world to prevent violence. This study examines the effectiveness of the “We Can Resolve Our Conflicts” conflict resolution training program in a sample of Western Thrace Minority elementary school students. It aims to enhance student conflict resolution skills by teaching constructive ways, to increase emotional regulation, social behavior skills, and reduce conduct problems. We used a pre-test post-test control group design. Our training group consisted of 103 students and our control group consisted of 74 students. Conflict resolution skills were assessed by conflict scenarios. Emotion regulation skills were measured using Emotion Regulation Checklist. Pro-social behavior skills and conduct problems assessed using Strengths and Difficulties Questionnaire. We Can Resolve Our Conflicts” program is a school-based prevention program consisting of 21 sessions with materials like caricatures, posters, and cartoons. We trained students to recognize emotions, empathy, control anger, and resolve conflicts constructively. Different techniques were employed, such as classroom discussions, role-playing, and penciland-paper activities to ensure active student participation. Control group students did not receive this training. We tested the “We Can Resolve Our Conflicts” program in a different location with similar cultural characteristics, and its effectiveness was approved. Findings showed that the training program raised students’ constructive conflict resolution skills, emotion regulation skills, and pro-social behavior skills. It reduced the level of conduct problems. The control group exhibited no changes in their conflict resolution and pro-social behavior skill scores from the pre to post-test. However, their emotion regulation and conduct problems scores changed negatively. In general, the findings of this study revealed that conflict resolution education is effective in resolving conflicts in elementary school students.